Client Satisfaction with Public Housing Maintenance Contractors: A Case Study of Nairobi City County (International Journal of Scientific Research and Management (IJSRM), 2020)
Coupled with the challenge of housing shortage in view of the growing urban population in Nairobi City County currently at 4.4 Million, the public housing sector is faced with deteriorating quality housing particularly for the low income residents and Public residential units, characterized by a poor state of maintenance. The foregoing points to an infringement of the right of access to adequate and decent housing as a basic right for every Kenyan as entrenched in the bill of rights in the constitution of Kenya, 2010. In an effort to transform the foregoing scenario, the County Government of Nairobi, through its Urban Renewal, Housing and Projects Management sector procures maintenance and other technical services from private sector contractors for renovation of old NCCG housing units and public housing amenities including water and sanitation, among other services. It however remains unexplored in the Kenyan body of knowledge, the extent to which NCCG is satisfied with the maintenance services by private contractors. Against this backdrop, the study set out to assess client satisfaction with public housing maintenance contractors with reference to Nairobi City County. The study adopted the descriptive study design, sampling 43 staff from NCCG’s, Urban Renewal, Housing and Projects Management sector. data was collected by use of structured questionnaires and analyzed by descriptive and inferential statistics. Findings indicate that the maintenance strategy adopted has a significant effect (β=.332, P value=.050=.05) on client satisfaction with service delivery by public housing maintenance contractors. The study however found that the procurement method adopted does not have a significant effect (β=.078, P value=.639>.05) on client satisfaction with service delivery by public housing maintenance contractors. The study recommends a combination of preventive, predictive and condition-based maintenance as they assure the longevity of public houses and avoidance of longer term costly and frequent renovations.